2015
DOI: 10.1063/1.4936133
|View full text |Cite
|
Sign up to set email alerts
|

Energy landscape of LeuT from molecular simulations

Abstract: The bacterial sodium-coupled leucine transporter (LeuT) has been broadly used as a structural model for understanding the structure-dynamics-function of mammalian neurotransmitter transporters as well as other solute carriers that share the same fold (LeuT fold), as the first member of the family crystallographically resolved in multiple states: outward-facing open, outward-facing occluded, and inward-facing open. Yet, a complete picture of the energy landscape of (sub)states visited along the LeuT transport c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 46 publications
3
46
0
Order By: Relevance
“…The conformation of TM1A has been investigated in two recent simulation reports. TM1A was shown to have a high probability to partially close the inner vestibule in a 1-palmitoyl-2-oleyl-phosphatidylethanolamine (POPE) membrane [42]. The opposing result was reported earlier, as TM1A was found to be very stable when residing in the hydrophobic core of a POPC membrane (stabilized by ~20 kJ/mol) [36].…”
Section: Discussionmentioning
confidence: 99%
“…The conformation of TM1A has been investigated in two recent simulation reports. TM1A was shown to have a high probability to partially close the inner vestibule in a 1-palmitoyl-2-oleyl-phosphatidylethanolamine (POPE) membrane [42]. The opposing result was reported earlier, as TM1A was found to be very stable when residing in the hydrophobic core of a POPC membrane (stabilized by ~20 kJ/mol) [36].…”
Section: Discussionmentioning
confidence: 99%
“…We note that, to the best of our knowledge, the simulations of the inward-facing conformation of LeuT-Y268A presented here are unique, because all previous studies either examined the inward-facing conformation after restoring the missing Tyr at position 268 (10,22,45,49) or considered the allosteric effect of the Y268A modification in the outward-occluded conformation (11). Although the available evidence shows that the Y268A modification strongly affects the ability for LeuT to stabilize outward-facing conformations and to allosterically detect ligand binding in those conformations (11), comparison of our simulation data with that reported for previous studies (10,22) revealed no obvious difference due to the Y268A modification in the nature of the inward-facing conformations, presumably because position 268 was entirely solvent exposed, and therefore unable to mediate direct interactions.…”
Section: Agreement Between Experimental and In Silico-predicted Deutementioning
confidence: 99%
“…6A). Indeed, the extent of TM1a movement has been a source of contention in the field given that the crystal conditions contained mostly detergent and only a minute quantity of lipid [1,2-dimyristoyl-sn-glycero-3-phosphoethanolamine (DMPE)], and that biophysical and computational studies have indicated a more restrained tilt of the helix (10,15,22,45). Our HDX-MS data demonstrate that TM1a (amino acids 17-28) as well as the attached N-terminal peptide (amino acids 1-16) were less protected against deuterium exchange under the inward-favoring conditions and thus apparently free to sample a larger conformational space with greater solvent accessibility than was available under the outward-favoring conditions (Figs.…”
Section: Agreement Between Experimental and In Silico-predicted Deutementioning
confidence: 99%
“…39 No dimeric structure has been resolved to date for IF LeuT dimer. However, comparison of LeuT crystal structures shows that the interfacial helices TM9 (K376-F395) and TM12 (V483-R507) undergo minimal movements, if any, between the OF and IF states.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Among them, our previous studies 39,40 were (to the best of our knowledge) the only simulations of LeuT wild-type (WT) dimer dynamics. The IF o dimer conformation was generated therein using the dimerization interface observed in the OF o crystal structure as a template.…”
Section: Introductionmentioning
confidence: 99%